COMMON CHALLENGES IN DEVELOPING WRITING AND READING SKILLS (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Annotation This article, authored by Shamsiddinova Sevara Ilhom kizi, explores the challenges that students face in developing writing and reading skills, which are fundamental to academic success and personal development. It identifies key obstacles such as language limitations, cognitive impediments, lack of access to resources, low motivation, and sociocultural influences. The article emphasizes the importance of understanding these challenges to design effective interventions and teaching strategies.